Analysis of ODP point placement using algorithm K-means in RW. 01 Gendongan village (case study: PT. Indomedia) - Setyadi, Candra; Chandra, Dian W. (Journal of Soft Computing Exploration, 2024)
This study discusses the placement of ODP points for designing Fiber To The Home (FTTH) networks in RW. 01 Gendongan Village using the K-Means algorithm. The purpose of this study is to facilitate the determination of the optimal location of the Optical Distribution Point (ODP) without the need for manual determination by the network designer. The initial stage of the study began with five stages, namely Determining the location of the study, Conducting surveys and data collection, Determining the location of the ODP placement using K-Means, Network design, Finished. The K-Means algorithm is used to determine the best ODP placement point after the study was conducted. The results of this study are divided into two stages, namely determining the location of the ODP placement and creating an FTTH access network scheme using Google Earth Pro software. The results obtained from using the K-Means algorithm with a value of K = 8 need to be adjusted. ODP adjustments are made to ODPs located in houses or in the middle of the road which will later be shifted to the shoulder of the road. Distribution cable design is carried out at the location of the ODP point that has been adjusted. The design of this distribution cable has 4 paths, each path has 2 ODPs. Previous research has focused on residential areas with relatively small coverage, while the current research covers a wider area, namely RW. This significant difference shows a shift in focus from a small scale to a larger scale so that it can optimize the deployment of FTTH networks in wider areas and improve more services.